1997
DOI: 10.1097/00001756-199705260-00035
|View full text |Cite
|
Sign up to set email alerts
|

Temporal window of integration revealed by MMN to sound omission

Abstract: The central auditory system for event perception involves the integrating mechanism of sequential information addressed by the present study. The mismatch negativity (MMN) component of the event-related potentials (ERP) reflects the automatic detection of sound change. ERPs to occasionally omitted stimuli were measured when sequences with constant stimulus onset asynchronies (SOAs) were presented. In separate blocks, the SOA was from 100 to 350 ms. A clear MMN was elicited by a stimulus omission in a sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
199
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(215 citation statements)
references
References 7 publications
14
199
1
1
Order By: Relevance
“…Our results confirm earlier findings that the omission of an expected tone leads to a time-locked brain response, which is easily detectable by MEG and EEG and has a topography similar to the original evoked response (16)(17)(18). Furthermore, our design tested the prediction, unique to the hierarchical predictive coding framework, that the omission response should vary with the context.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results confirm earlier findings that the omission of an expected tone leads to a time-locked brain response, which is easily detectable by MEG and EEG and has a topography similar to the original evoked response (16)(17)(18). Furthermore, our design tested the prediction, unique to the hierarchical predictive coding framework, that the omission response should vary with the context.…”
Section: Discussionsupporting
confidence: 88%
“…It is a rather remarkable fact that the auditory cortex generates extensive responses locked to the absence of a predictable sound. This omission response can be detected by a variety of methods, including event-related potentials (ERPs) (16), magnetoencephalography (MEG) (17), and intracranial recordings (18). Omission responses fit quite naturally within the predictive coding framework: If stimulus-evoked brain activity indexes the difference between a sensory signal and its top-down prediction, then, when the sensory signal is omitted, the evoked activity should reflect the pure prediction signal within the same cortical area (8,19,20).…”
mentioning
confidence: 99%
“…Critically, this and other previous studies using tone omissions [e.g., Yabe et al (1997Yabe et al ( , 1998Yabe et al ( , 2001, Shinozaki et al (2003), and Winkler et al (2005)] did not manipulate the sequential predictability of the omitted tone. The present study reveals that initial processing similarities are only observed with full predictability of the omitted tone, but not with partial predictability as given in the restorable and control conditions.…”
Section: Discussionmentioning
confidence: 47%
“…Note that the current stimulus paradigm and analyses were not optimized toward testing the omission-related MMN, and that the predictability effect was found substantially earlier than the expected latency range of the omission-related MMN [100 -150 ms from the onset of the expected tone (cf. Yabe et al, 1997Yabe et al, , 1998…”
Section: Discussionmentioning
confidence: 99%
“…One of the most remarkable properties of the auditory system is that it can generate evoked responses to an absent but expected stimulus (Joutsiniemi and Hari, 1989;Raij et al, 1997;Yabe et al, 1997;Hughes et al, 2001;Todorovic et al, 2011;Wacongne et al, 2011). We similarly tested the response of our network to the omission of an expected sound.…”
Section: Mmn To Omissionmentioning
confidence: 99%